2017
DOI: 10.1002/2016jb013865
|View full text |Cite
|
Sign up to set email alerts
|

Upper crustal investigation of the Gulf of Saint Lawrence region, eastern Canada using ambient noise tomography

Abstract: We studied the 3‐D shear wave velocity (Vs) structure in the Gulf of St. Lawrence (GSL) and adjacent onshore areas to 20 km depth by inverting Rayleigh wave dispersion extracted from the vertical components of continuous ambient seismic noise waveforms. The region is divided into three broad zones based on their Vs characteristics. In the northwest, the Grenville Province (i.e., the exposed edge of predominantly Middle‐Proterozoic Laurentian crust) is dominated by high Vs, except for well‐known anorthosite sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 109 publications
(180 reference statements)
1
15
0
Order By: Relevance
“…This sedimentary basin has a U‐shaped geometry with the maximum thickness located beneath PEI. Our interpretations are consistent with the previous ANT study carried out over the GSL (Kuponiyi et al., 2017). The next thickest sedimentary layer is located under the NE St. Lawrence River and beneath the Humber margin with a thickness of ∼5–6 km.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This sedimentary basin has a U‐shaped geometry with the maximum thickness located beneath PEI. Our interpretations are consistent with the previous ANT study carried out over the GSL (Kuponiyi et al., 2017). The next thickest sedimentary layer is located under the NE St. Lawrence River and beneath the Humber margin with a thickness of ∼5–6 km.…”
Section: Discussionsupporting
confidence: 94%
“…The Gulf of St. Lawrence at depths < $< $20 km is dominated by slow anomalies (Kao et al., 2013). A regional‐scale study carried out over this area suggests a maximum sedimentary thickness of ∼8 km beneath this region (Kuponiyi et al., 2017). It is also suggested that the Grenvillian basement beneath the northern Appalachians is wedged out at depth by the Red Indian Line (Kuponiyi et al., 2017).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…A northwest‐dipping fabric at lower crust to mantle depths is imaged in central Newfoundland that likely indicates a relict subduction zone (e.g., van der Velden et al., 2004). Further west, upper‐ to mid‐crustal depths beneath the Gulf of Saint Lawrence were studied using a surface wave tomography method, and westward dipping of Avalonia beneath Ganderia was interpreted (Kuponiyi et al., 2017). Continental‐scale seismic tomography models at crustal depths show an overall decrease of seismic velocities from the eastern Grenville to the northern Appalachians but lack enough resolution to provide more detailed tectonic interpretations (e.g., Kao et al., 2013).…”
Section: Introductionmentioning
confidence: 99%